A Influência de manobras de válvulas na identificação do fator de atrito em tubulações de rede de distribuição de água - Viana, Francisco Marques (2014)
An important advance in the hydraulic network modeling was the calibration through this is possible to know the behavior of the physical characteristics of the network, which is of great importance in decision-making. In this work we will use the reverse transient method applied with genetic algorithm for calibration of friction factors pipes of a water distribution network through simulations from the variation of parameters as the number of chromosomes, number of generations, passing a point mutation and simple, we measured quantity, and different types of maneuvering valve (sudden and soft). The simulations were divided into instances, wherein each solution found by computational model was evaluated by an objective function based on square difference between observed and calculated results for the transient loads in (s) node (s) monitored (s). The analyzes of the solutions shown as the inverse method, the algorithm genetic and the choice of its parameters influence the final result. Through cases, it was observed that for the studied networks, no use simply alone increase values ​​of the parameters of the genetic algorithm in order to improve the efficiency of method. As this is an inverse method, a specific combination of friction factor was generated from the average of these solutions under the same parameters in ten successive applications of genetic algorithm (processing). The results reported for hydraulic loads in (s) node (s) monitored (s) were very close considered the actual loads (Observed), in some parts of pipes values ​​for the friction force and considered close to real. The efficiency of the results was measured by Function Objetiv